2015
DOI: 10.1142/s0217732315501230
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian error distribution of 7Li abundance measurements

Abstract: We construct the error distribution of 7 Li abundance measurements for 66 observations (with error bars) used by Spite et al. (2012) that give A(Li) = 2.21± 0.065 (median and 1σ symmetrized error). This error distribution is somewhat non-Gaussian, with larger probability in the tails than is predicted by a Gaussian distribution. The 95.4% confidence limits are 3.0σ in terms of the quoted errors. We fit the data to four commonly used distributions: Gaussian, Cauchy, Student's t, and double exponential with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The results of this study agree with earlier research that also observed Student-t tails, but only looked at a handful of subatomic or astrophysics quantities up to z ∼ 5 − 10 [16,19,[56][57][58]. Unsurprisingly, the tails reported here are mostly heavier than those reported for repeated measurements made with the same instrument (ν ∼ 3−9) [59][60][61], which should be closer to Normal since they are not independent and share most systematic effects.…”
Section: A Comparison With Earlier Studiessupporting
confidence: 90%
“…The results of this study agree with earlier research that also observed Student-t tails, but only looked at a handful of subatomic or astrophysics quantities up to z ∼ 5 − 10 [16,19,[56][57][58]. Unsurprisingly, the tails reported here are mostly heavier than those reported for repeated measurements made with the same instrument (ν ∼ 3−9) [59][60][61], which should be closer to Normal since they are not independent and share most systematic effects.…”
Section: A Comparison With Earlier Studiessupporting
confidence: 90%
“…More specifically, we examine the Gaussianity of these error distributions. 2 We begin by following and Crandall & Ratra (2015) and construct an error distribution, a histogram of measurements as a function of N σ , the number of standard deviations that a measurement deviates from a central estimate. This is similar to the z score analysis of de Grijs et al (2014), however, we use a central estimate from the data compilation itself whereas de Grijs et al (2014) use two published values that are assumed to well represent the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Ratra et al ( [4]), we calculated the estimates using two methods: median statistics and weighted mean estimates. The weighted mean (Θ M ) is given by [25]:…”
Section: A Error Distribution and Distribution Functionsmentioning
confidence: 99%
“…In the last decade, Ratra and collaborators have used a variety of astrophysical datasets to test the non-Gaussianity of the error distributions from these measurements. The datasets they explored for this purpose include measurements of H 0 [3], Lithium-7 measurements [4] (see also [5]), distance to LMC [6], distance to galactic center [7]. Evidence for non-Gaussian errors has also been found in HST Key project data [8].…”
Section: Introductionmentioning
confidence: 99%